The Utilization of TiO2 Nanotechnology in Organic Pesticides as a Solution to the Hazards of Synthetic Pesticides - Audy Via Rahmawai; Nur Jamilah; Ranaa Aufaa Azmi Wardana; Firyal Chumala Adhwa’; Adelita Ramadhani; Adhelia Maulidatul Jazirah; Ayunda Putri Khasanah (International Forum of Researchers and Lecturers, 2026)
The use of synthetic pesticides in the agricultural sector remains the primary choice for farmers in Indonesia due to their high effectiveness, but their massive use has negative impacts on human health and the environment. Therefore, there is a need for environmentally friendly and sustainable pesticide innovations. Red onion peel waste with the addition of TiO₂ nanotechnology is a strategic development step as a solution to the dangers of synthetic pesticides. Red onion peel contains bioactive compounds such as acetogenin, squamocin, gibberellin, cytokinin, and abscisic acid, which have the potential to be natural pest control agents. The process of making organic pesticides is carried out through the maceration of onion skins, followed by the addition of TiO₂ nanoparticles that act as photocatalytic catalysts to increase pesticide effectiveness and degrade synthetic pesticide residues. The development of these organic pesticides is in line with the principles of Green Chemistry, particularly designing safer chemicals, catalysis, design for degradation, and real-time pollution prevention. Through the implementation of strategic steps such as research, testing, socialization, and continuous evaluation, TiO₂ nanotechnology-based organic red onion peel pesticides have the potential to become a safe, effective, and environmentally friendly alternative in supporting sustainable agriculture in Indonesia.